Substance Use among Homeless Reproductive Age People in Southern Ethiopia - Wakgari, Negash; Woyo, Terefe; Kebede, Emnet; Gemeda, Hirut; Binu, Wakgari; Moti, Gonfa (International Journal of Reproductive Medicine, 2021)
Introduction. Substance use by homeless reproductive age people may result to anxiety, involvement of risky sexual behaviors, and increasing the likelihood of unwanted pregnancy and sexually transmitted diseases (STDs). Therefore, this study assessed the magnitude of alcohol use, sexual intercourse after alcohol use, and its associated factors among homeless reproductive age people in southern Ethiopia. Methods. Community-based cross-sectional study design was conducted among homeless reproductive age people. The snowball sampling technique was used to recruit 842 participants. Pretested and structured interviewer-administered questionnaire was used to collect the data. Data were entered into Epidata version 3.1 and exported to SPSS version 23 for analysis. Binary logistic regression was used to determine the association of independent variables with the outcome variables. Odds ratio with their 95% confidence interval and P value was used to identify the significant variables. Results. More than half 423 (53.2%) of the respondents had taken a drink that contains alcohol in the last one year of the study period. Out of 324 khat chewers, 190 (58.64%) had sex after chewing khat. More than one-thirds, 323(38.4%) homeless people were smoking cigarette during the study period. Factors associated with alcohol use were age 19-25 years (AOR: 0.49; CI: 0.34, 0.72), ≥26 years (AOR: 0.40; CI: 0.25, 0.65), level of education (AOR: 0.61; CI: 0.39, 0.94), place of residence: major urban (AOR: 0.31; CI: 0.18, 0.51), small town (AOR: 0.38; CI: 0.23, 0.63), ever heard about STDs (AOR: 0.14; CI: 0.07, 027), and being a cigarette smoker (AOR: 2.67; CI: 1.94, 3.71). Conclusions. In this study, significant percentage of respondents had taken a drink that contains alcohol. Age, level of education, place of residence, ever heard about STDs, and smoking cigarette were variables significantly associated with alcohol use. Awareness creation on the effect and outcome of substance use is recommended.